(untitled) (New York, 1985)
Comprehensive yet concise, this work functions as ``both a history of Britian and an historical dictionary.'' Organized in chronological chapters and thematic sections, it surveys British and Irish history from 100 B.C. to A.D. 1975. Marginal notes act as descriptive specific entries, with the main text providing interpretative background articles. A biographical ``Who's Who'' lists leading figures, and crisp maps and illustrations enhance the text
Keywords: Nước Anh,Ai len; Lịch sử,Lịch sử